PENGARUH PENGGUNAAN E-MODUL BERBASIS COMPUTATIONAL THINKING TERHADAP PEMAHAMAN KONSEPTUAL SISWA SMK - Meyda; Jaka (Information Technology Education Department, 2026)
The low le ve l of conce ptual unde rstandi ng among vocati onal hi gh school stude nts i n le arni ng i s ofte n cause d by a le arni ng proce ss that te nds to focus on me mori zi ng formulas rathe r than logi cal re asoni ng. The purpose of thi s study i s to analyze the e ffe ct of usi ng Computati onal Thi nki ng (CT)-base d e -modul on the conce ptual unde rstandi ng of vocati onal hi gh school stude nts. Thi s study i s a quanti tati ve study usi ng a quasi -e xpe ri me ntal me thod. The de si gn e mploye d i s a non-e qui vale nt control group de si gn. The sample consi ste d of 80 te nth-grade stude nts at SMK Sukatani Purwakarta, di vi de d i nto an e xpe ri me ntal class and a control class. The re sults of the study show a si gni fi cant e ffe ct on stude nts' conce ptual unde rstandi ng, as e vi de nce d by the si gni fi cance value of the I nde pe nde nt Sample T-Te st of 0.001 (p < 0.05). The ave rage N-Gai n score i n the e xpe ri me ntal class re ache d 0.72 (hi gh cate gory), whi le the control class only score d 0.28 (low cate gory). The e ffe ct si ze te st usi ng Cohe n's d produce d a value of 0.812, whi ch falls i nto the strong e ffe ct cate gory. The re sults i ndi cate that CT-base d e -module s are e ffe cti ve i n e nhanci ng vocati onal hi gh school stude nts’ abi li ty to gai n a de e p unde rstandi ng of conce pts through syste mati c thi nki ng. Keywords: Computati onal Thi nki ng; Conce ptual Unde rstandi ng; E -moduls; Vocati on Hi gh School Stude nt.